Impact of otosclerosis symptoms on patients quality of life before and after surgery – a literature review - Kuchar, Iga; Kościelska, Oktawia; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2020)
Otosclerosis is a chronic process that leads to hearing impairment and other onerous symptoms, such as tinnitus or dizziness. The following conclusions can be drawn from the analysis: they lead to problems in communication with the environment, as well as to different types of disorders of psychological nature, and this negatively affects the quality of life of patients. Despite the great progress in knowledge, the disease process cannot be completely stopped with otosclerosis. The most effective method of treatment is stapes surgery, which main goal is to improve speech hearing and understanding, as well as to reduce the accompanying symptoms. The greatest recognition among doctors collect stapedotomy surgery. The surgery may have unpleasant complications for some patients, but it is worth noting that in the majority of cases these problems disappear after a maximum of a few weeks. The aim of the study was to analyse previously published articles and other scientific literature on the impact of symptoms associated with otosclerosis on the quality of life of patients. Due to the small number of relevant publications, the search time frame has not been limited. The search for the literature needed to write the article was conducted using the Google Scholar and PubMed scientific articles databases. The topics of the described works included: generally quality of life, what is the sense of hearing for a person, the effects of hearing loss on the patient's functioning, the impact of tinnitus on the patient's life, possible methods of treatment for otosclerosis, improved hearing after surgery, as well as possible postoperative complications and their impact on well-being of the patient.